2014
DOI: 10.1007/s10714-014-1700-8
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and research for future detectors

Abstract: Technologies, design aspects and recent progresses for future gravitational wave (GW) detectors are mentioned in this summary of the C4 session of the Amaldi 10 conferenc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Recent work [10] has shown that the room temperature bulk optical absorption at 1550 nm of some commercially available material is at a level suitable for its use as a mirror substrate in a GW detector, and further investigations [11] indicate that the cryogenic absorption is similar. Operating at cryogenic temperatures requires control of heat input to the test mass, to keep the mass at the operating temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work [10] has shown that the room temperature bulk optical absorption at 1550 nm of some commercially available material is at a level suitable for its use as a mirror substrate in a GW detector, and further investigations [11] indicate that the cryogenic absorption is similar. Operating at cryogenic temperatures requires control of heat input to the test mass, to keep the mass at the operating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsically, the optical absorption in pure silicon above 1450 nm is negligible (<10 −8 cm −1 ) [9], but impurities can cause absorption directly, or by providing additional free carriers within the material. Recent work [10] has shown that the room temperature bulk optical absorption at 1550 nm of some commercially available material is at a level suitable for its use as a mirror substrate in a GW detector, and further investigations [11] indicate that the cryogenic absorption is similar. Operating at cryogenic temperatures requires control of heat input to the test mass, to keep the mass at the operating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we investigate a novel approach for the earthbound detection of GWs at frequencies around 0.1-10 Hz by utilizing repeatedly free falling test masses [22,23]. By overcoming limits that are related with seismic attenuation and suspension thermal noise, we aim to complement advanced detectors at their lower frequency range.…”
Section: Introductionmentioning
confidence: 99%